High-yield preparation of edge-functionalized and water dispersible few-layers of hexagonal boron nitride (hBN) by direct wet chemical exfoliation. (13th July 2021) - Yu, Le; Yap, Pei Lay; Tran, Diana N H; Santos, Alexandre M C; Losic, Dusan
Abstract: Owing to many fascinating properties including high thermal and chemical stability, excellent electrical insulation, fire-retardant and antibacterial properties, hexagonal boron nitride (hBN) has emerged as a prominent 2D material for broad applications. However, the production of high quality of hBN by chemical exfoliation from its precursor is still challenging. This paper presents a high-yield (+83%), low-cost and energy-efficient wet chemical exfoliation strategy, which produces few-layers (FL, 3–6 layers) of edge-functionalized (OH) hBN nanosheets with uniform size (486 ± 51 nm). This optimized preparation is established based on a comprehensive investigation on the key exfoliation parameters such as exfoliation temperature, time and amount of the oxidant (potassium permanganate). High quality of FL-hBN was confirmed by various characterization techniques including scanning electron microscopy coupled with energy dispersive X-ray, transmission electron microscopy, Raman, Fourier transform infrared spectroscopy, X-ray diffraction and X-ray photoelectron spectroscopy analyses. The outcome of this study paves a promising pathway to effectively produce hBN through a cost-efficient exfoliation approach, which has a significant impact on industrial applications.